2017
DOI: 10.1016/j.apcatb.2017.02.066
|View full text |Cite
|
Sign up to set email alerts
|

Visible-light-enhanced photothermocatalytic activity of ABO3-type perovskites for the decontamination of gaseous styrene

Abstract: ABO 3-type perovskites (A=La, Ce, Sm; B=Cr, Mn, Fe, Co, Ni) were systematically fabricated via a facile soft-templated sol-gel with post-calcination method through a complexation-carbonation-oxidation process, which were successfully applied in the visible-light-driven photothermocatalytic degradation of volatile organic compounds (VOCs) for the first time. Preliminary characterization results revealed the lower impact to the oxidative performance and visible-light-absorption properties of ANiO 3 than LaBO 3 ,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
40
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 115 publications
(42 citation statements)
references
References 49 publications
2
40
0
Order By: Relevance
“…Shen et al [54], in their interesting research on hybrid organic-inorganic perovskite for solar cell application, assigned this peak to the methyl group. The conclusion obtained here agrees well with that reported by previous literature confirming the achievement of the synthesis processes [18,[63][64][65][66].…”
Section: Photo-catalyst Characterizationsupporting
confidence: 93%
See 1 more Smart Citation
“…Shen et al [54], in their interesting research on hybrid organic-inorganic perovskite for solar cell application, assigned this peak to the methyl group. The conclusion obtained here agrees well with that reported by previous literature confirming the achievement of the synthesis processes [18,[63][64][65][66].…”
Section: Photo-catalyst Characterizationsupporting
confidence: 93%
“…Peak corresponding to 401 eV peak were assigned to N1s Figure 4D. In accordance with the studies performed by Chen et al [64], N state may vary and the associated peaks can be found at different BE. Different peaks positions were found in a range of 396-404 eV in agreement with Nakamura and Mrowetz et al [65].…”
Section: Photo-catalyst Characterizationsupporting
confidence: 86%
“…Recently, photocatalysis with a semiconductor has been proven to be efficient in the degradation of a wide range of organic pollutants as well as detoxification of hazardous compounds in practical applications. 16,[60][61][62]143 Recently, MOFs have also been demonstrated as semiconductors and are capable of generating reactive charges and transferring the photo-generated charges to reactive sites for in situ degrading organic compounds into CO 2 and water upon light irradiation, resulting in the regeneration of adsorbent MOFs and avoiding secondary pollution. The unique chemical and physical properties of MOFs hold great potential for photocatalytic degradation of VOCs.…”
Section: Mof-based Photocatalysts For Gaseous Pollutant Degradationmentioning
confidence: 99%
“…are continuously contributing to the VOCs emissions in indoor habitats [1,2,3,4,5]. There are currently different exploring technologies devoted to VOCs remediation including the use of plasma discharges [6,7,8,9], microwaves combining absorption–desorption–combustion steps [10,11,12], photodegradation [2,5,13,14,15,16,17,18,19,20], and adsorption/catalytic oxidation [2,21,22,23,24,25,26,27,28,29]. Total oxidation of VOCs promoted by conventional catalysts represents one of the most appealing alternatives.…”
Section: Introductionmentioning
confidence: 99%
“…Noble metals are able to completely oxidize VOCs into CO 2 and H 2 O at mild reaction temperatures [22,23,25,30,31,32,33,34,35,36,37,38,39]. Transition metal oxides and complex metal oxides (i.e., rare earth element-based perovskites) are also excellent VOCs oxidation candidates that operate at relatively mild temperatures without incurring in the burdening costs of noble metals [3,8,16,37,38,39,40,41,42,43,44,45]. Alternatively, the use of inexpensive arrays of photocatalysts based on titania (TiO 2 ) has become one of the most important research fields towards the sustainable remediation of VOCs [5,20,46,47,48,49,50,51].…”
Section: Introductionmentioning
confidence: 99%